ANALISIS PENGELOLAAN KEUANGAN OBJEK WISATA PINUS PA’TENGKO KECAMATAN MENGKENDEK KABUPATEN TANA TORAJA - Riani Rudin; Helba Rundupadang; Mince Batara (Smart Education, 2026)
This descriptive qualitative research aims to analyze the financial management of BUMDes in managing the Pinus Pa’tengko Tourism Object, Mengkendek District, Tana Toraja Regency. The analysis covers five stages: planning, execution, record-keeping, reporting, and accountability. Data were collected through observation, documentation studies, and semi-structured interviews with the Head of Lembang, the BUMDes Chairman, and the Treasurer. The results show that during planning, budgeting is participatory involving the community and traditional leaders, although revenue targets rely on rough estimates without detailed expenditure drafts. In execution, business units for ticketing, parking, ATV rentals, and camping successfully create local employment, despite facing tourist fluctuations and high maintenance costs for non-permanent facilities. In record-keeping, administrative dualism was identified: the Chairman claims to use digital applications, whereas the Treasurer still relies on manual daily cashbook recording. The reporting stage is hindered by unpunctual unit managers, misplaced transaction receipts, and unclear field reports. In accountability, the Accountability Report (LPJ) is submitted annually to the Lembang Government alongside net profit distributions (35% employee salaries, 30% retained earnings, 20% BUMDes, and village income contribution). However, periodic in-depth evaluations remain passive and are tightened only when financial irregularities are indicated.